PENGARUH KUALITAS PRODUK YANG DIPERSEPSIKAN,PERSEPSI HARGA, DAN CITRA MEREK TERHADAP MINAT BELI ULANG PRODUK LAPTOP ACER DI KOTA BANDUNG - Gumelar Hidayat, Rully; Faizal Fardhani Sigarlaki (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This research aims to analyze the influence of perceived product quality, perceived price, and brand image on repurchase interest in Acer laptop products in Bandung City. The analytical methods used are instrument validity and reliability tests, descriptive analysis, classical assumption analysis (normality test, multicollinearity test, and heteroscedasticity test), multiple regression test, and hypothesis testing using SPSS Version 25 tools. This research uses secondary data obtained from the Top Brand Index and primary data obtained through distributing online questionnaires involving 120 respondents. Of the four proposed research hypotheses, the results of this research show that the variables of perceived product quality, perceived price, and brand imagehave a positive effect on repurchase intention both partially and simultaneously. It is hoped that the results of this research will provide benefits for further research and benefits for the Acer Company regarding designing strategies that are relevant to improving the quality of these attributes.